Taxonomic status of the enigmatic salamander Cryptotriton adelos (Amphibia: Plethodontidae) from northern Oaxaca, Mexico, with observations on its skull and postcranial skeleton - Wake, David B.; Rovito, Sean M.; Maisano, Jessica A.; Hanken, James (Zootaxa, 2012)
Papenfuss and Wake (1987) described a new species of plethodontid salamander from northern Oaxaca, Mexico, which they named Nototriton adelos. The species was assigned to Nototriton primarily on the basis of its similarity to members of that widespread genus, which as then constituted ranged from Oaxaca, Mexico, to east-central Costa Rica. At that time, Nototriton had no unique synapomorphies but rather included diminutive species that could be excluded from membership in all other genera. Wake and Elias (1983), who erected Nototriton, acknowledged that the genus might eventually be shown to be paraphyletic, but they were unable to further resolve the phylogeny with information then available. The original description of N. adelos was based on the holotype and three paratypes; in the subsequent 25 years, despite many futile attempts, only one additional specimen of this species has been discovered: UTAVC A-3956, the largest known specimen, a female, 25.6 mm snout-vent length, from near the type locality.